BIOACTIVE FRACTION OF TROPIDIA CURCULIOIDES, A RARE ORCHID OF ARUNACHAL PRADESH, INDIA: PHYTOCHEMICAL PROFILE AND MARKER COMPOUNDS - Sarkar, Nandan; S Avasthi, Anupama; Ghosal, Sabari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Chemical profiling of the most active fraction of Tropidia curculioides, isolation and characterization of marker compounds along with the evaluation of biological activity. Methods: The most active Et2O fraction of roots of T. curculioides (TC) was analyzed by gas chromatography coupled with a mass selective detector. Repetitive chromatography followed by high-performance liquid chromatography of the active fraction afforded three major compounds. The structure of the compounds was established by nuclear magnetic resonance and mass spectral analysis. Antibacterial activity of the compounds was determined by agar well diffusion method against five multidrug-resistant (MDR) clinical isolates while minimum inhibitory concentration (MIC) and minimum bactericidal concentration were determined by microdilution method. Scanning electron microscopy was performed with compound 2 against Escherichia coli cells at MIC (15 Î¼g/ml). Results: Analysis of the gas chromatographyâ€“mass spectrometry (GCâ€“MS) spectra revealed that the isolated compounds constituted 27.16% of the total constituents. Two other chemical classes, namely, saturated fatty acids and sterol constituted 38.04% and 12.49%, respectively. The structure of the compounds was characterized as 4-hydroxy benzaldehyde (1), bisphenol F (2), and 3,5-dihydroxy-4-methoxybenzoic acid (3). The most significant bacteriostatic and bactericidal activity against E. coli comparable to that of tetracycline and gentamicin was observed with compound 2. Microscopic study confirmed that compound 2 affects integrity of cell membrane severely, causing death of the bacterium. Compound 1 and 3 showed moderate to good antibacterial activity against E. coli and Enterococcus sp. Cell cytotoxicity of the compounds was well within permissible limit. This is the first report of compounds in TC. Conclusion: The study identified three marker compounds from the less polar fraction of the roots of TC with significant antibacterial activity. The GCâ€“MS spectra with marker compounds could be treated as the chemical fingerprinting of the bioactive fraction. The outcome justifies the use of the plant in traditional medicine.